(3EYGOI GdJCejf Hjf GdfXQjI h GdJWHjb (B/s - (3TcQj, HgGA HgjLs ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2011)
1) (3GdJYQja HGYGOI GdJCejf (B: (3fThA h JWhQ GYGOI GdJGejf , YbO GYGOI GdJGejf h GLQGAGJg h YehdGJg (B2) (3WQb GYGOI GdJCejf (B: (3GYGOI GdJGejf GdGNJjGQj , GdZWGA GdeaJhM , GYGOI GdJGejf GdGJaGbj (B: (3GJaGbjI GdeTGQcI , GJaGbjI GdaGFV , GJaGbjI RjGOI GdNSGQI , GJaGbjI GdNSGQI GdMOjI h GJaGbjGJ eNJdaI , WQbI CNQi dGYGOI GdJGejf (B: (3GdZWGA GdeROhL , GYGOI GdJGejf GdeJbGHd h GdMSGH GdeTJQc (B3) (3JWHjbGJ GYGOI GdJGejf (B: (3JZWjI eMaXI GdMQjb (B: (3JZWjI cGed GdeMaXI h GdJZWjI GdeLRCI , JZWjI eMaXI GdMhGOK (B: (3JZWjI GdMhGOK GdYGeI h JZWjI GdJCejf GdgfOSj , JZWjI eMaXI CNWGQ Gdfbd (B: (3JZWjI aQY JCejf GdSaf h JZWjI aQY GdHVGFY , GYGOI JGejf MhGOK GdWjQGf , JZWjI eMaXI GdMjGI (B4) (3YbO h WQb GdGSfGO GdecQQ (B5) (3GdHJGejf GdGSdGej h YdGbJg HGYGOI GdJGejf GdJLGQj (B: (3GdJGejf h GYGOI GdJGejf GdJLGQj Hjf GdJMdjd h GdJMQje , eGgjI GdJGejf GdGSdGej , GdJGejf GdGSdGej h GYGOI GdJGejf h GNjQG GdWQb GdebJQMIs
Keywords: (3EYGOI GdJCejfs; (3GdJCejf (B- (3GdHfhcs; (3GdJCejf(B- (3GdeNGWQs